The SketchUp workflow for architecture : modeling buildings, visualizing design, and creating construction documents with SketchUp Pro and LayOut - Brightman, Michael, 1980- 4 0 16; 5 (Hoboken, NJ : Wiley, 2018)
This book is for architects and related design professionals who want to take their SketchUp use to the next level. In-depth tips and techniques show users how to use SketchUp and its related suite of tools in every stage of the design process. The author presents a flexible workflow that makes common design tasks easier and allows users to incorporate varying degrees of SketchUp use into their design process. Included are best practices for organizing projects, drafting schematics. A section devoted to LayOut guides readers through an often underused component of SketchUp Pro. Tutorial videos compliment the book, demonstrating some of the more advanced methods--
Front Matter -- Starting the Flow -- Starting the Flow. Introduction -- Building Information Modeling -- Hardware -- File and Folder Management -- SketchUp -- SketchUp. SketchUp Basics -- The Professional's SketchUp Template -- The Professional's SketchUp Environment -- SketchUp Collections -- Extensions -- LayOut -- LayOut. Introduction to LayOut -- The LayOut Interface -- The Professional's LayOut Environment -- LayOut Tools -- Inserting Content -- Model Organization -- Model Organization. Model Organization Overview -- New Construction -- Renovation -- Visualization -- Visualization. Introduction to Visualization/Preparation -- Rendering -- Altered Reality -- Construction Documents -- Construction Documents. Crucial Concepts for Construction Documents -- Title Blocks -- Drawings -- Annotations -- Exporting -- Index.
Includes index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; SketchUp.;SketchUp.; Computer-aided design.;Data processing. -- Architectural drawing;Architectural design -- 20; 20; Electronic books. -- 2